Durability simulation of elastomeric materials using finite element method (FEM) - Chieh, C. W.; Ali, Aidy; Sanuddin, Asmawi; Hosseinabadi, Reza Afshar (2009)
The paper presents the simulation work on the elastomer subjected to cyclic loads. A 3D finite element model of elastomer specimen which in accordance with ASTM D412 was developed using CATIA and ANSYS commercial finite element (FEM) packages. The fatigue life predicted from simulation was compared with a well documented published data and show acceptable agreement. The simulated strain-life results are slightly lower than the experimental data. Several factors that potentially influenced the variation of the results were noted. Finally, some recommendations have been made at the end of this study to further improve the simulation.